System‐Specific Variability in Murray Cod and Golden Perch Maturation and Growth Influences Fisheries Management Options. (2nd December 2015) - Forbes, Jamin P.; Watts, Robyn J.; Robinson, Wayne A.; Baumgartner, Lee J.; Allen, Micheal S.; McGuffie, Prue; Cameron, Leo M.; Crook, David A.
Abstract: The Murray Cod Maccullochella peelii and Golden Perch Macquaria ambigua are important recreational species in Australia's Murray–Darling Basin (MDB); both species have declined substantially, but recovery is evident in some areas. Minimum length limits (MLLs)—implemented to ensure fish could spawn at least once prior to harvest eligibility—have increased three times in the past decade. We quantified variation in length at 50% maturity (LM50), age at 50% maturity (AM50), and von Bertalanffy growth parameters ( k = Brody growth coefficient; L ∞ = asymptotic length; t 0 = theoretical age at zero length) of these species within two rivers and two reservoirs of the MDB; to investigate whether fish length is a suitable surrogate for AM50 in setting MLLs. Between 2006 and 2013, we collected 1, 118 Murray Cod and 1, 742 Golden Perch by electrofishing and gillnetting. Values of k and L ∞ were greater for reservoir fish than for riverine fish. For both species, AM50 was generally greater in rivers than in reservoirs; for Murray Cod, LM50 was greater in reservoirs than in rivers. A yield‐per‐recruit model demonstrated that smaller Murray Cod MLLs would be required for rivers and that an MLL at or below 600 mm (the existing MLL) across all populations could lead to overfishing in some systems. The differences in growth rate and the onset of reproductive maturation between riverine and reservoir populations suggest that system‐specific regulations would be more effective at reducing the overfishing risk and meeting fishing quality objectives. Received August 18, 2014; accepted September 10, 2015